The renin-angiotensin-aldosterone system, neurohumoral axis and cardiovascular mortality in LURIC - Yazdani, Babak; Delgado Gonzales de Kleber, Graciela; Kleber, Marcus E.; Yücel, Gökhan; Husain-Syed, Faeq; Kraemer, Thomas D.; Jochims, Jan Alexander; Leipe, Jan; März, Winfried; Krämer, Bernhard (The journal of clinical hypertension, 2022)
Although neurohormones and Renin-Angiotensin-Aldosterone-System (RAAS) components are important predictors of cardiovascular mortality (CVM), their importance for predicting outcomes in patients with/without RAAS-blockers and different degrees of arterial stiffness is less understood. We therefore analyzed long-term data from the Ludwigshafen Risk and Cardiovascular Health (LURIC) study in 3316 patients subdivided according to pulse pressure (PP) and RAAS-blocker use. Patients on RAAS-inhibition had higher renin and noradrenaline, lower aldosterone and aldosterone/renin quotient (ARQ). Renin and noradrenaline significantly predicted CVM in patients without RAAS-blocker (HR = 1.17, 1.15) and in patients receiving angiotensin-converting-enzyme (ACE) inhibitors (HR = 1.17, 1.29), whereas aldosterone predicted CVM only in patients receiving ACE-inhibitors (HR = 1.13). CVM was predicted independently from PP by renin, noradrenaline and angiotensin II. Independently from RAAS inhibition renin decreased and ARQs increased with rising PP. Furthermore, noradrenaline increased with PP, but only without ACE-inhibition. The HR for CVM in the ACE-inhibitor group were 1.29, 1.28, 1.29 for renin in the first, second and third PP quartiles and 1.22, and 1.19 for aldosterone in the second and fourth quartile. Furthermore, we showed that noradrenaline predicts CVM in all PP quartiles in patients with ACE-inhibition. In the RAAS-blocker-free group, the HR for renin for CVM were 1.36 and 1.18 in the third and fourth PP quartiles, but neither aldosterone nor noradrenaline were predictive for CVM within the PP quartiles. Renin and noradrenaline are strong predictors of CVM regardless of RAAS blockade, whereas aldosterone is predictive only in the ACE-inhibitor group. Catecholamines but not renin are associated with rising PP.
Gesehen am 27.06.2023